1973
DOI: 10.4315/0022-2747-36.3.129
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio Parahaemolyticus: Infection or Toxicosis?1

Abstract: The facultative halophile Vibrio parahaemolyticus, since its first isolation, has been shown to be toxic for mice and has produced experimental infection when fed to animals and humans. Pathogenicity has been shown to be associated with the presence of a heat-stable hemolysin-the Kanagawa-hemolysin. Previously, investigators reported that most strains of V. parahaemolyticus, regardless of virulence, could produce dilatation in the ligated rabbit gut. We have shown however, that ileal loop reactivity is strongl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
1

Year Published

1974
1974
1986
1986

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 0 publications
2
27
1
Order By: Relevance
“…This finding is in contrast to that of Twedt (1972) who found that cell-free culture filtrate had no effect on the ileal loop. Culture filtrates employed in the study by Twedt were concentrated by dialysis against Carbowax (Twedt, personal communication).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This finding is in contrast to that of Twedt (1972) who found that cell-free culture filtrate had no effect on the ileal loop. Culture filtrates employed in the study by Twedt were concentrated by dialysis against Carbowax (Twedt, personal communication).…”
Section: Discussioncontrasting
confidence: 99%
“…The pathogenicity of V. parahaemolyticus in relation to the Kanagawa reaction was first studied with the ligated gut loop tests in rabbits by Twedt (1972). He stated that ileal loop reactivity was strongly associated with their Kanagawa hemolysin production by the vibrios.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies proved again that the Kanagawa phenomenon is associated with virulence of the strains (Twedt and Brown, 1973;Sakazaki et al, 1974). It remains to be clarified, however, how this property is acquired.…”
Section: Discussionmentioning
confidence: 99%
“…Rabbit ileal loop test. The reactivity of test cultures was determined by a modification of the rabbit ileal loop technique (26,27) in which 1-ml portions of adjusted BHI-salt cultures were injected randomly into individual loops. Sterile broth and known culture controls were used.…”
Section: Methodsmentioning
confidence: 99%